2016
DOI: 10.1088/1748-9326/11/5/054016
|View full text |Cite
|
Sign up to set email alerts
|

When will unusual heat waves become normal in a warming Africa?

Abstract: Africa is one of the most vulnerable continents to climate change. In the upcoming decades the occurrence of longer, hotter and more frequent heat waves could have a strong impact on human mortality and crop production. Here, by applying the heat wave magnitude index daily to temperature reanalysis data, we quantify the magnitude and the spatial extent of the most extreme heat waves experienced in Africa between 1979 and October 2015 across different seasons. Results show that in the recent years Africa experi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
162
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 193 publications
(174 citation statements)
references
References 34 publications
12
162
0
Order By: Relevance
“…The frequency of tropical cyclones may remain unchanged but they are predicted to become more intense in some ocean basins (Seneviratne et al, ). Moreover, the duration and intensity of droughts will increase in some regions of the world, including southern and central Europe, central North America, Central America and Mexico, north‐east Brazil and southern Africa (Handmer et al, ; Pohl et al, ; Russo et al, ; Seneviratne et al, ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The frequency of tropical cyclones may remain unchanged but they are predicted to become more intense in some ocean basins (Seneviratne et al, ). Moreover, the duration and intensity of droughts will increase in some regions of the world, including southern and central Europe, central North America, Central America and Mexico, north‐east Brazil and southern Africa (Handmer et al, ; Pohl et al, ; Russo et al, ; Seneviratne et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…This pattern is likely to accelerate. For example, increases in daily temperature and precipitation extremes are likely to continue, more extreme rainfall is expected in southern Africa, increased drought intensity is expected in central America, north‐east Brazil and the Mediterranean, and drought and heat waves are expected to become more frequent in Australia, northern Africa and south‐western America (Handmer et al, ; Pohl, Macron, & Monerie, ; Russo, Marchese, Sillmann, & Imme, ; Seneviratne et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…Regional studies of heat extremes have also demonstrated how strongly low baseline variability-as is found in the tropics and to a lesser extent the subtropics-influences frequency of occurrence and time of emergence, with tropical regions such as northern Australia and much of Africa [114] projected to see large increases despite only moderate amounts of absolute warming [112,115]. On a percentile basis relative to the current climatology, Russo et al [13] project that by 2100, under the RCP 8.5 pathway, events as anomalous locally as the Russia 2010 heatwave was will occur as frequently as every year in much of the tropics and the drier parts of the midlatitudes.…”
Section: Projected Changes In Heat Event Recurrence and Time Of Emergmentioning
confidence: 99%
“…Such temperature increase is expected to continue in the future with a projected global temperature change of about 1.4°C to 4.8°C (Intergovernmental Panel on Climate Change, 2014) and a regional response over the Sahel of about 2°C to 6°C (Sylla, Nikiema, et al, 2016) when considering the Representative Concentration Pathway 4.5 and 8.5 concentration scenarios (Moss et al, 2012). As a result, hot extremes will become more common and deadly in many regions across the world (Gasparrini et al, 2017;Im et al, 2017;Lee & Kim, 2016;Mora et al, 2017) and in tropical Africa (Giorgi et al, 2014;Liu et al, 2017;Russo et al, 2014), with their frequency, duration, and magnitude depending on the underlying forcing scenario (Anderson et al, 2018;Dosio, 2017;Linares et al, 2014;Russo et al, 2016). Such hot extremes can have widespread impacts on human and natural systems, thereby challenging the adaptive capacity and resilience of local populations and activities (Ceccherini et al, 2017;Fontaine et al, 2013;Pal & Eltahir, 2016;Sultan & Gaetani, 2016;Zougmoré et al, 2016).…”
Section: Introductionmentioning
confidence: 99%